Optimalisasi Dakwah Melalui Pemanfaatan Teknologi Informasi dan Komunikasi di DKM Al-Hikmah Kabupaten Bandung Barat pada Masa Pandemi Covid-19 - Wisnuadhi, Bambang; Setiawan, Setiawan (Ma'soem University, 2022)
During the COVID-19 pandemic, many community activities were limited by the government to break the chain of spreading the deadly virus. One of the activities that is limited is preaching which is one of the informal religious activities that have the aim of teaching the basics of religion to the general public. In order to maintain the continuing missionary activities, the Community Services Team of the Politeknik Negeri Bandung is moving to help provide real solutions for worshipers of the Al-Hikmah Mosque in West Bandung Regency. Activities carried out by the Participatory Action Research method to be able to answer the problems encountered. The results of the activity showed that the Community Services Team of the Politeknik Negeri Bandung together with the Al-Hikmah Mosque congregation succeeded in creating a Youtube channel as a preaching tool. In addition, pilgrims are more active in communicating and asking questions in the WhatsApp group.